Assignment of individuals to four poultry breeds of India using multilocus genotypes - VIJH, R K; TANTIA, M S (The Indian Journal of Animal Sciences, 2014)
Assignment of individuals to a breed was attempted using multilocus genotypes in 4 poultry breeds of India utilizing 26 microsate lite loci. The unknown indiciduals were asigned on the basis of reference allelic frequencies of the 4 poultry breeds. Genetic data analysis methods like frequeny method, Bayesian method and genetic distances like Nei’s standard. Net’s minimum, Net’s DA, Allele sharing and chord distance were utilized. All the individuals were assigned to the populations correctly with 100% accuracy. The method of population exvlusion was also employed with the above 3 methods using exvlusion threshold of 0.01. The average probability of wrong assignment was very low. The likelihood method performed better than the frequency method for assignment of unknown individuals. Among genetic distances DAS and chord distance gave better assignments than the Nei’s genetic distances.